Implementation of a Course Bibliography Management Service (BLIC) at university library in Colombia - Chisaba Pereira, Cristian Alejandro (2026)
This research on the development of a service of Bibliography Management of Courses was motivated from the analysis and the concern to make decisions on the bibliography present in the syllabus of the subjects of the Pontificia Universidad Javerian. The objective of this article was to analyze and propose a service of management that involves the processes, technology and methodology for it. Through the analysis of literature, the analysis of course bibliography data and the evaluation of functional requirements for a course bibliography management software was obtained a process involving the different processes of collection management and the E-software was selected Reserves for the administration of bibliographies.